Post a New Question

algebra

posted by on .

given f(x)=2x^2-4 and g(x)=5x+3
1. f(a)
2. f(3a)
3. f(a+b)
4. f(x+7)
5. f(5x+3)
6. g(f(x))

  • algebra - ,

    The function notation of f(x)=2x²-4 means that the letter "x" on each side of the equal sign takes on the same value. So
    f(3) = 2(3)²-4 = 18-4 = 14
    f(a) = 2(a)²-4 = 2a²-4
    f(b+c) = 2(b+c)²-4 = 2b + 2c -4
    etc.

    since g(x)=5x+3,
    f(g(x)) = f(5x+3) = 2(5x+3)² - 4
    Expand the expression on the right hand side to get the final answer.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question